EVALUACIÓN FINANCIERA AL BAZAR “PRO-HOGAR” DE LA CIUDAD DE LOJA, PERIODO 2014-2015 - Paladínez Castillo, Verónica Lizette (2017)
The thesis entitled financial evaluation the Bazaar "Pro-Hogar" from the city of Loja, period 2014-2015, was realized, given its relevance in the increasingly competitive business environment, with the firm purpose of analyzing and evaluating the Results obtained from the analysis and interpretation of the financial statements of the "Pro-Hogar" bazaar, which will help to minimize risks and take advantage of the opportunities and financial resources to improve its profitability. In fulfillment of the general objective, "To carry out a financial evaluation to the Pro-Hogar bazaar of the city of Loja, during the period 2014-2015" it became essential the fulfillment of each one of the specific objectives by which the application proceeded to realize Of the horizontal and vertical analysis that allowed to have information of the degree of participation of each one of the items in the economic-financial structure and the variations produced from one period to another, giving greater relevance to the most significant changes. The different financial indicators of liquidity, indebtedness, activity and profitability were applied through which it was possible to know that the bazaar does not have sufficient liquidity to cover short-term obligations, the rotation of accounts receivable and inventories in periods Analyzed more than 30 days so that collection strategies should be maintained as they are the key to the income of cash and also implement promotions that contribute to the rotation of inventories, in addition the company has a low level of indebtedness with suppliers and No type of indebtedness with financial institutions, which shows that the bazaar operates with own capital. Subsequently, it was possible to know that the cash conversion cycle of the bazaar maintains an extended time for its inventories and accounts 5 receivable to generate cash after covering its obligations with suppliers. In the DuPont system, it was determined that the profitability of the bazaar has decreased significantly from one period to another due to the unnecessary expenses incurred, thus demonstrating an inadequate management of resources. The break even point represents the level of sales that is required for the bazaar to cover its total costs, showing that if it exceeds this value the company will incur profits and if it happens otherwise the bazaar will get lost. Finally, a financial evaluation report was presented, which includes the results obtained with the respective conclusions and recommendations, the same ones that have been proposed with the purpose of improving the profitability of the company, for which the following most relevant conclusion was determined : The bazaar has serious collection problems, ie it is not recovered within the established time of 30 days, because customers cancel these accounts in a period of 75 days, causing the bazaar problems to cancel their suppliers, It is suggested to implement adequate collection policies, making a more adequate register of their clients.